Direct-write technologies for rapid prototyping applications : sensors, electronics, and integrated power sources - Pique, Alberto; Chrisey, Douglas B. (Academic Press, 2002)
Direct-Write Technologies covers applications, materials, and the techniques in using direct-write technologies. This book provides an overview of the different direct write techniques currently available, as well as a comparison between the strengths and special attributes for each of the techniques. The techniques described open the door for building prototypes and testing materials. The book also provides an overview of the state-of-the-art technology involved in this field. Basic academic researchers and industrial development engineers who pattern thin film materials will want to have this text on their shelves as a resource for specific applications. Others in this or related fields will want the book to read the introductory material summarizing isuses common to all approaches, in order to compare and contrast different techniques. Everyday applications include electronic components and sensors, especially chemical and biosensors. There is a wide range of research and development problems requiring state-of-the-art direct write tools. This book will appeal to basic researchers and development engineers in university engineering departments and at industrial and national research laboratories. This text should appeal equally well in the United States, Asia, and Europe. Both basic academic researchers and industrial development engineers who pattern thin film materials will want to have this text on their shelves as a resource for specific applications. This book provides An overview of the different direct write techniques currently available A comparison between the strengths and special attributes for each of the techniques An overview of the state-of-the-art technology involved in this field.